Design And Implementation Of Music Information System Web Based - Silvia Ningsih (Journal Of Global Research Publications, 2024)
Information is the result of data processing in a form that is more useful and more meaningful for the recipient that describes real events (facts) that are used for decision making. The music information system website aims to provide various communication and information services about music. The information system used by the music community so far is considered slow and complicated. Both musicians and producers have difficulty communicating directly and the number of individuals who can communicate directly is relatively small. Therefore, the current system cannot meet the demands of the information needs, it needs to be developed so that it can display information and communication facilities about music directly and quickly. In designing the music information system website using Php & MySql Script. Where in the design of this information system itself uses a Database where the use of the Database itself is as a media that manages all data and a place to store the data itself later. The information system itself is designed so that musicians and producers can create their own profiles. This information system also provides communication services about music. The final result achieved from this music information system is as a communication service for the music community, Sharing Content, publication, and promotion from musicians to the public and producers.